Native Broadcasting in Canada - Rupert, Robert (Anthropologica, 2022)
This article examines recent efforts to create native radio and television stations in Canada. In the beginning, trail and community radio provided the initial model for native Canadian broadcasting. Eventually, the Northern Native Broadcast Access Program, sponsored by the Native Citizens Directorate of the Secretary of State, led to further developments. In the last few years, native Canadian broadcasters have created many innovations and have successfully confronted the challenge of presenting serious discussions of native issues to a native audience which was previously accustomed to commercial, light entertainment programing from southern Canada and the United States